Is a single dose of commonly used antibiotics effective in preventing maternal infection after cesarean section? A network meta-analysis. - Ye Huang; Xinbo Yin; Xiaokai Wang; Fangyi Zhou; Xiaoxia Cao; Yeqiong Han; Shichang Sun (PLoS ONE)
Objective This study aimed to compare the efficacy of different antibiotic classes and dosages in preventing maternal infection after cesarean delivery. Methods Databases were searched for randomized controlled trials (RCTs) published between January 1980 and January 2021 on antibiotic use for the prevention of maternal infection after cesarean delivery. The outcomes were endometritis, febrile morbidity, and wound infection, reported as odds ratios (OR) and surface under the cumulative ranking curve analysis scores. Results A total of 31 RCTs met the inclusion criteria. In the network meta-analysis (NMA) for endometritis, pooled network OR values indicated that the following interventions were superior to placebo: cephalosporins (OR: 0.18, 95% credibility interval [CrI]: 0.07-0.45), penicillins (OR: 0.19, 95% CrI: 0.07-0.50), penicillins (multiple doses) (OR: 0.20, 95% CrI: 0.05-0.65), combination therapies (OR: 0.22, 95% CrI: 0.09-0.54), and cephalosporins (multiple doses) (OR: 0.25, 95% CrI: 0.08-0.74). In the NMA for febrile morbidity, placebo was more effective than the other interventions. In the NMA for wound infection, pooled network OR values indicated that the following interventions were superior to placebo: penicillin (OR: 0.14, 95% CrI: 0.05-0.37), cephalosporins (OR: 0.19, 95% CrI: 0.08-0.41), cephalosporins (multiple doses) (OR: 0.20, 95% CrI: 0.06-0.58), combination therapies (OR: 0.29, 95% CrI: 0.13-0.57), macrolides (OR: 0.33, 95% CrI: 0.15-0.74), and penicillins (multiple doses) (OR: 0.40, 95% CrI: 0.17-0.91). Conclusions Compared with placebo, a single dose of commonly used antibiotics may prevent maternal infection after cesarean delivery. However, the incidence of febrile morbidity was not reduced.